Determination of Dynamic Deflected Mode of Cylindrical Pipe Under the Impact of a Seismic Type - Djumaev Z.F (Genius Journals, 2022)
The article covers the problem of determination of dynamic deflected mode of a cylindrical pipe under the influence of a seismic wave. The design diagram is shown in Fig. 1. Known from the dynamic theory is solved by the method based on summation theorem. The summation theorem for cylindrical wave functions is derived in the work of elasticity, and the equation of motion in vector form for an isotropic body is obtained in the following form
Keywords: equation; obtained; derived; mode